تقويم الظروف الهيدروجيولوجية لطبقة المياه الجوفية الحرة في المنطقة الواقعة بين نهري السن والروس في الساحل السوري - حايك شريف; الأسعد علي; محمد ديمة (Latakia University Journal -Engineering Sciences Series, 2018)
تقع منطقة البحث في الساحل السوري بين نهري السن والروس. ويهدف البحث إلى دراسة الخصائص الهيدروجيولوجية للطبقة الحاملة للمياه الجوفية الحرة في منطقة البحث، وتقويم ظروف توضعها، حيث اعتمد البحث على شبكة رصدٍ تتألف من 36 بئراً للمراقبة تخترق الطبقة الحاملة الجوفية الحرة، واستمرّت القياسات فيها خلال الفترة (تشرين الأول 2016 حتى أيلول 2017). تتراوح أعماق المياه الجوفية الحرة في منطقة البحث بين 0.5-11.5 m، وتصل أحياناً خلال فترة الجفاف إلى 13.5m، بينما تكون قريبة من سطح الأرض شتاءً وتصل إلى 0.1m في بعض الآبار. كما تتراوح الناقلية الكهربائية للمياه الجوفية بين (550-3700) µs حيث تزداد كلما اتجهنا غرباً وتبلغ 9000 µs وأكثر في الآبار القريبة من البحر خلال فترة الجفاف. تنخفض مناسيب المياه الجوفية إلى مستوى أدنى من منسوب سطح البحر في الآبار القريبة من الشاطئ مما يحقق الشروط الهيدروديناميكية لاندساس مياه البحر ضمن الطبقة الحاملة للمياه الجوفية الحرة. The research area is located in the Syrian coast between the Sin and Rous river. This research aims at studying the hydrogeological characteristics of the unconfined aquifer in the research area and evaluating the conditions of its placed. The research was based on a monitoring network consisting of 36 wells that penetrate the unconfined aquifer, and measurements continued during the period (October 2016 until September 2017). The unconfined groundwater depths in the research area range between 0.5-11.5 m, and sometimes during the drought period reach to 13.5 m, while it is close to the surface in the winter and up to 0.1m in some wells. The electrical conductivity ranges between 550-3700 μs/cm, increasing as we go west and reaching 9,000 μs/cm and more in the wells near the sea during the dry period. Groundwater levels Lower in the dry period to below sea level in near-shore wells, achieves the hydrodynamic conditions of the seawater intrusion.